1993
DOI: 10.1002/ajmg.1320450508
|View full text |Cite
|
Sign up to set email alerts
|

Association between alleles of the transforming growth factor‐alpha locus and the occurrence of cleft lip

Abstract: DNA samples from 100 patients with cleft lip with or without cleft palate (CL/P) were compared with those of 98 unaffected control individuals with respect to transforming growth factor alpha (TGFA) genotypes. Among the Caucasians in this population (83 CL/P, 84 controls), there was a significant difference in the restriction fragment length polymorphisms (RFLPs) observed after digestion with TaqI (chi 2 = 4.68, P = 0.03). The frequency of the C2 allele in the Caucasian CL/P population was 0.169, whereas that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…Tel : j39-0532-291538; Fax: j39-0532-291533; E-mail: tgm!unife.it located on 2p13, and the occurrence of clefting. Since then, several investigations supported a role for TGFA, or a nearby gene (OFC2), as a susceptibility gene(s) involved in some way in OFC malformations (Chenevix-Trench et al 1992 ;Holder et al 1992 ;Sassani et al 1993 ;Feng et al 1994 ;Jara et al 1995). In a recent linkage study using markers mapping on 2p13, we confirmed the genetic heterogeneity for OFC, and evidence of linkage was observed in the same group of families showing linkage to 6p23 markers .…”
Section: supporting
confidence: 77%
See 1 more Smart Citation
“…Tel : j39-0532-291538; Fax: j39-0532-291533; E-mail: tgm!unife.it located on 2p13, and the occurrence of clefting. Since then, several investigations supported a role for TGFA, or a nearby gene (OFC2), as a susceptibility gene(s) involved in some way in OFC malformations (Chenevix-Trench et al 1992 ;Holder et al 1992 ;Sassani et al 1993 ;Feng et al 1994 ;Jara et al 1995). In a recent linkage study using markers mapping on 2p13, we confirmed the genetic heterogeneity for OFC, and evidence of linkage was observed in the same group of families showing linkage to 6p23 markers .…”
Section: supporting
confidence: 77%
“…Also, many molecular genetic investigations supported major gene\oligogenic models in the development of the cleft, with evidence for loci in different chromosome regions. For example there was evidence for a locus on 6p23 (OFC1) (Eiberg et al 1987 ;Carinci et al 1995 ;Davies et al 1995 ;Scapoli et al 1997), on 2p13 (OFC2) (Ardinger et al 1989 ;Chenevix-Trench et al 1991Holder et al 1992 ;Sassani et al, 1993 ;Mitchell, 1997), 19q13 (OFC3) (Stein et al 1995 ;Wyszynski et al 1997 ;Martinelli et al 1998), on 4q25-31 (Beiraghi et al 1994 ;Healey et al 1994), and on 17q21 (RARA) (Chenevix- Trench Shaw et al 1993), all of which appeared to be involved in clefting.…”
Section: mentioning
confidence: 99%
“…The association of the TFGa alleles with CL(P) has been confirmed by others (e.g., Chenevix-Trench et al, 1991;Holder et al, 1992;Sassani et al, 1993). ChenevixTrench et al (1992) also found an association between CL(P) and altered frequency of different RARa alleles, as did Shaw et al (1993).…”
Section: ) Genetic Factors (A) Role Of Genetic Factors In the Etiolomentioning
confidence: 60%
“…Recognized associations include chromosomal abnormalities, Mendelian disorders, and various teratogenic agents (Gorlin et al, 1990). Recently, genetic studies have defined an association between genetic variation at the transforming growth factor-alpha locus and non-syndromic orofacial clefting (Ardinger et al, 1989;Chenevix-Trench et al, 1991Holder et al, 1992;Sassani et al, 1993;Shiang et al, 1993).…”
Section: Etiology Of Ntds and Craniofacial Malformationsmentioning
confidence: 99%
“…Recognized associations include chromosomal abnormalities, Mendelian disorders, and various teratogenic agents (Gorlin et al, 1990). Recently, genetic studies have defined an association between genetic variation at the transforming growth factor-alpha locus and non-syndromic orofacial clefting (Ardinger et al, 1989;Chenevix-Trench et al, 1991Holder et al, 1992;Sassani et al, 1993;Shiang et al, 1993).There are a number of epidemiologic characteristics that are unique to craniofacial malformations. For example, it appears as if male infants have a higher incidence of cleft lip with or without cleft palate than do female infants, whereas the reverse is true for isolated cleft palate (Fraser, 1970;Emanuel et al, 1983;Shaw et al, 1991).…”
mentioning
confidence: 99%